Management strategy of post-operative spinal infection - Islam, M. Anowarul; Saha, Asim Kumar; Fahim, Zafri Ahmed; Islam, Afia Ibnat; Aziz, Sanjida (International Journal of Research in Medical Sciences, 2025)
Background: This study aims to evaluate the outcomes of different management strategies in PSIs, with a focus on infections caused by S. epidermidis and TB organisms. Specific emphasis is placed on the role of antimicrobial and anti-TB drug therapies, as well as revision surgical procedures. Methods: Analysis was conducted on 31 patients diagnosed with PSI at Bangladesh Medical University between 2015 and 2023. 14 patients received targeted antimicrobial therapy for pyogenic infections 5 patients received anti-TB therapy for tubercular infections. Revision surgical management, 7 patients underwent debridement only, 3 patients underwent debridement with fusion and 2 patients underwent debridement with fixation. Assessment were done at 1st, 3rd, 6th and 12th monthly by VAS, Odom Criteria, Nurick’s grading. Data were analyzed via the Statistical Package for Social Sciences (SPSS). A p value <0.05 was considered statistically significant. Results: The mean VAS score significantly improved from 6.27±1.75 to 0.73±0.59 at 12 months (p < 0.001). According to the Modified Odom Criteria, 33.3% of patients had excellent outcomes, 60.0% had good outcomes and 6.7% had fair outcomes. Functional status measured by Nurick’s grading improved significantly, with 93.3% of patients in Grade III preoperatively and 87% improving to either Grade 0 or I by 12th months (p<0.001). Conclusions: Effective management of PSIs depends on early diagnosis, appropriate antimicrobial or anti-TB therapy and timely surgical intervention. Staphylococcus epidermidis infections respond well to targeted antimicrobial therapy and debridement, whereas TB infections require prolonged anti-TB regimens and often more extensive surgical stabilization.